The role of strategic alliances in gaining sustainable competitive advantage for firms - Refik Culpan (Management Revue, 2008)
This article offers a critical assessment of the role of strategic alliances in gaining sustainable competitive advantage through building knowledge assets. To do so, it develops a conceptual model, in which three key concepts: the role of 'knowledge assets' in gaining 'sustainable competitive advantage' via 'strategic alliances' between firms are defined and related to each other. It argues core competencies and dynamic capabilities of firms depend on knowledge assets of the firm. In turn, knowledge assets of the firm determine its sustainable competitive advantage. Furthermore, it explicates how knowledge assets can be exploited or explored in a strategic alliance context. In addition, by offering a new conceptual model, this article contributes to our understanding of the linkages among knowledge building and collaborative ventures between firms and stimulates further research on strategic alliances.
Keywords: 650; strategic alliances; sustainable competitive advantage; knowledge assets; components of knowledge; knowledge exploitation and exploration